2022
DOI: 10.1021/acs.jpclett.2c02614
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroarenes: A Versatile Platform for Hybrid Perovskite Photovoltaics

Abstract: The instability of hybrid organic–inorganic halide perovskites presents one of the pressing challenges for their application. This is associated with the sensitivity to moisture as well as mixed ionic–electronic conductivity that leads to enhanced ion migration under conditions of voltage and light bias. Some of the most effective strategies to stabilize hybrid perovskite materials during operation involve the use of interfacial molecular assemblies and low-dimensional perovskite architectures based on hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Reactions usually proceed through the functionalization of the most electrophilic fluorinated carbon (in the ortho-positions to the fluorinated atoms and in the para-position to the nonfluorine substituent). However, cases of selective functionalization of other positions are also known (see Schemes 5,27,28,35 and 36). In addition, a mechanistic test with bromo-or chloropolyfluoroarenes to determine the reaction mechanism is highly recommended for such reactions.…”
Section: Polyfluoroarenes As Radical Acceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions usually proceed through the functionalization of the most electrophilic fluorinated carbon (in the ortho-positions to the fluorinated atoms and in the para-position to the nonfluorine substituent). However, cases of selective functionalization of other positions are also known (see Schemes 5,27,28,35 and 36). In addition, a mechanistic test with bromo-or chloropolyfluoroarenes to determine the reaction mechanism is highly recommended for such reactions.…”
Section: Polyfluoroarenes As Radical Acceptorsmentioning
confidence: 99%
“…[1][2][3] While processes relying on specific fluorine effects associated with fluoroalkyl moieties have been extensively reviewed, the ability of fluorinated aromatic groups to serve as reactivity-enabling functionality has long been neglected, and existing reviews focus on the functionalization of the polyfluoroarene core. [4][5][6][7][8][9][10][11][12][13][14][15][16] At the same time, polyfluoroarenes are widely used for different purposes of catalysis, [17][18][19][20][21] analytical chemistry, 22,23 biochemistry, [24][25][26][27] and materials science [28][29][30][31] and their applications are well beyond the C-F bond activation. This review aims to highlight the known applications of polyfluoroarenes in organic chemistry of free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an un-encapsulated (F-PEA) 2 MA 2 Pb 5 I 16 device maintained 65% of its initial PCE after 576 h at 70 °C. In the future, it may be possible to include the use of perfluoroarene-based cations 65 and their 1 : 1 mixtures with arene spacers (which went as far back as in 2003) 66 applicable to the DJ phase 67 for controlling the crystallographic characteristics and their associated properties for solar cell demonstrations.…”
Section: Layered Perovskite Applicationsmentioning
confidence: 99%
“…It has been shown that fluorinated arylammonium cations in 2D perovskites improve the hydrophobic character of the interlayer region and further enhance the stability of the inorganic layers. Different isomers of a chemically tuned PEA molecule have been studied to tune the properties and efficiency of the layered structures. Zhang et al have investigated the effects of functionalizing the benzene ring of PEA with F at the para position to the ethylammonium moiety.…”
Section: Introductionmentioning
confidence: 99%